Deglaciation of the Burren glacio‐karst, western Ireland, during Termination 1: Implications for North Atlantic climate and karstification - Gordon Bromley; Colin Bunce; Brenda Hall; Aaron Putnam; Frank McDermott (Journal of Quaternary Science, 2026)
The Burren uplands in western Ireland form one of the most extensive and best‐preserved examples of glacio‐karst in Europe. Subsumed by the Irish ice sheet during the Late Pleistocene, granite erratic boulders and in situ silica veins in the limestone bedrock provide a rare opportunity to reconstruct the timing and rate of deglaciation following the Last Glacial Maximum (LGM) using cosmogenic beryllium‐10 ( 10 Be) surface‐exposure dating. Such information is key to establishing seasonal climatic conditions in the circum‐North Atlantic during the last glacial termination, particularly Heinrich Stadial 1 (HS1: ~18.0–14.7 ka), and quantifying landscape denudation rates in temperate maritime karst systems. This study reports a new deglacial chronology from the Burren, constrained with in situ 10 Be and supported by minimum‐limiting U‐Th and 14 C ages, that reveals pronounced thinning and retreat of terrestrial ice between ~18.0 and 17.0 ka. In conjunction with existing measurements of Burren karst features, we applied the new age constraint for postglacial exposure to refine long‐term denudation rates, which are broadly similar to other maritime European karstlands. The close agreement between the 10 Be surface‐exposure ages and independent ages for Burren deglaciation also permits an empirical test of our chosen production rate and confirms it is applicable to this period and these latitudes. From a palaeoclimatological perspective, the Burren 10 Be record indicates deglaciation during HS1, a pattern that we propose supports recent hypotheses invoking globally warming Heinrich summers despite anomalous wintertime cooling of the circum North Atlantic.

Challenges and Strategic Recommendations for Enhancing Quantification and Projection of Forest Carbon Dynamics - Holly L. Munro; Christopher W. Woodall; William R. L. Anderegg; Jeff W. Atkins; Colin M. Beier; Bronson P. Bullock; Kendall DeLyser; David D. Diaz; Bianca N.I. Eskelson; Margaret E. K. Evans; John D. Foppert; Bryan C. Foster; et al. (Journal of Forestry, 2025)

Energizing tourism sustainably: A harmonious symphony of tourists’ and locals’ acceptance of renewable energy - Fahimeh Hateftabar; Colin Michael Hall (Journal of Environmental Management, 2023)

Lowering temperature to 1 °C results in physiological changes, stress and mortality in cultured Atlantic Salmon (Salmo salar) - Émile Vadboncoeur; Charlotte Nelson; Jennifer R. Hall; Kathy A. Clow; Rebeccah M. Sandrelli; Colin J. Brauner; Andrew K. Swanson; A. Kurt Gamperl (Aquaculture, 2023)

Paleolimnological evaluation of metal(loid) enrichment from oil sands and gold mining operations in northwestern Canada - Mitchell L. Kay; Izabela Jasiak; Wynona H. Klemt; Johan A. Wiklund; Jelle A. Faber; Lauren A. MacDonald; James V.K. Telford; Cory A.M. Savage; Colin A. Cooke; Brent B. Wolfe; Roland I. Hall (Environmental Research, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

High-Resolution Spatiotemporal Dynamics of Harmful Algae in the Indian River Lagoon (Florida)—A Case Study of Aureoumbra lagunensis, Pyrodinium bahamense, and Pseudo-nitzschia - Cary B. Lopez; Charles L. Tilney; Eric Muhlbach; Josée N. Bouchard; Maria Célia Villac; Karen L. Henschen; Laura R. Markley; Stephanie Keller Abbe; Sugandha Shankar; Colin P. Shea; Leanne Flewelling; Matthew Garrett; et al. (Frontiers in Marine Science, 2021)
The Indian River Lagoon (IRL), located on the east coast of Florida, is a complex estuarine ecosystem that is negatively affected by recurring harmful algal blooms (HABs) from distinct taxonomic/functional groups. Enhanced monitoring was established to facilitate rapid quantification of three recurrent bloom taxa, Aureoumbra lagunensis , Pyrodinium bahamense , and Pseudo-nitzschia spp., and included corroborating techniques to improve the identification of small-celled nanoplankton (<10 μm in diameter). Identification and enumeration of these target taxa were conducted during 2015–2020 using a combination of light microscopy and species-specific approaches, specifically immunofluorescence flow cytometry as well as a newly developed qPCR assay for A. lagunensis presented here for the first time. An annual bloom index (ABI) was established for each taxon based on occurrence and abundance data. Blooms of A. lagunensis (>2 × 10 8 cells L –1 ) were observed in all 6 years sampled and across multiple seasons. In contrast, abundance of P. bahamense , largely driven by the annual temperature cycle that moderates life cycle transitions and growth, displayed a strong seasonal pattern with blooms (10 5 –10 7 cells L –1 ) generally developing in early summer and subsiding in autumn. However, P. bahamense bloom development was delayed and abundance was significantly lower in years and locations with sustained A. lagunensis blooms. Pseudo-nitzschia spp. were broadly distributed with sporadic bloom concentrations (reaching 10 7 cells L –1 ), but with minimal concentrations of the toxin domoic acid detected (<0.02 μg L –1 ). In summer 2020, multiple monitoring tools characterized a novel nano-cyanobacterium bloom (reaching 10 9 cells L –1 ) that coincided with a decline in A. lagunensis and persisted into autumn. Statistical and time-series analyses of this spatiotemporally intensive dataset highlight prominent patterns in variability for some taxa, but also identify challenges of characterizing mechanisms underlying more episodic yet persistent events. Nevertheless, the intersect of temperature and salinity as environmental proxies proved to be informative in delineating niche partitioning, not only in the case of taxa with long-standing data sets but also for seemingly unprecedented blooms of novel nanoplanktonic taxa.

Response to “Connectivity and pore accessibility in models of soil carbon cycling” - Bonnie G. Waring; Benjamin N. Sulman; Sasha Reed; A. Peyton Smith; Colin Averill; Courtney A. Creamer; Daniela F. Cusack; Steven J. Hall; Julie D. Jastrow; Andrea Jilling; Kenneth M. Kemner; Markus Kleber; et al. (Global Change Biology, 2021)
Here we respond to Baveye and colleagues' recent critique of our PROMISE model, describing how this new framework significantly advances our understanding of soil spatial heterogeneity and its influence on organic matter transformations.

Response to ‘Stochastic and deterministic interpretation of pool models’ - Bonnie G. Waring; Benjamin N. Sulman; Sasha Reed; A. Peyton Smith; Colin Averill; Courtney A. Creamer; Daniela F. Cusack; Steven J. Hall; Julie D. Jastrow; Andrea Jilling; Kenneth M. Kemner; Markus Kleber; et al. (Global Change Biology, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

From pools to flow: The PROMISE framework for new insights on soil carbon cycling in a changing world - Bonnie G. Waring; Benjamin N. Sulman; Sasha Reed; A. Peyton Smith; Colin Averill; Courtney A. Creamer; Daniela F. Cusack; Steven J. Hall; Julie D. Jastrow; Andrea Jilling; Kenneth M. Kemner; Markus Kleber; et al. (Global Change Biology, 2020)
Soils represent the largest terrestrial reservoir of organic carbon, and the balance between soil organic carbon (SOC) formation and loss will drive powerful carbon‐climate feedbacks over the coming century. To date, efforts to predict SOC dynamics have rested on pool‐based models, which assume classes of SOC with internally homogenous physicochemical properties. However, emerging evidence suggests that soil carbon turnover is not dominantly controlled by the chemistry of carbon inputs, but rather by restrictions on microbial access to organic matter in the spatially heterogeneous soil environment. The dynamic processes that control the physicochemical protection of carbon translate poorly to pool‐based SOC models; as a result, we are challenged to mechanistically predict how environmental change will impact movement of carbon between soils and the atmosphere. Here, we propose a novel conceptual framework to explore controls on belowground carbon cycling: P robabilistic R epresentation of O rganic M atter I nteractions within the S oil E nvironment (PROMISE). In contrast to traditional model frameworks, PROMISE does not attempt to define carbon pools united by common thermodynamic or functional attributes. Rather, the PROMISE concept considers how SOC cycling rates are governed by the stochastic processes that influence the proximity between microbial decomposers and organic matter, with emphasis on their physical location in the soil matrix. We illustrate the applications of this framework with a new biogeochemical simulation model that traces the fate of individual carbon atoms as they interact with their environment, undergoing biochemical transformations and moving through the soil pore space. We also discuss how the PROMISE framework reshapes dialogue around issues related to SOC management in a changing world. We intend the PROMISE framework to spur the development of new hypotheses, analytical tools, and model structures across disciplines that will illuminate mechanistic controls on the flow of carbon between plant, soil, and atmospheric pools.

In Memoriam of Dr. Kevin Robertson - Colin David Hall (Journal of NeuroVirology, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Marine Microphytobenthic Assemblage Shift along a Natural Shallow-Water CO2 Gradient Subjected to Multiple Environmental Stressors - Vivienne Johnson; Colin Brownlee; Marco Milazzo; Jason Hall-Spencer (Journal of Marine Science and Engineering, 2015)
Predicting the effects of anthropogenic CO2 emissions on coastal ecosystems requires an understanding of the responses of algae, since these are a vital functional component of shallow-water habitats. We investigated microphytobenthic assemblages on rock and sandy habitats along a shallow subtidal pCO2 gradient near volcanic seeps in the Mediterranean Sea. Field studies of natural pCO2 gradients help us understand the likely effects of ocean acidification because entire communities are subjected to a realistic suite of environmental stressors such as over-fishing and coastal pollution. Temperature, total alkalinity, salinity, light levels and sediment properties were similar at our study sites. On sand and on rock, benthic diatom abundance and the photosynthetic standing crop of biofilms increased significantly with increasing pCO2. There were also marked shifts in diatom community composition as pCO2 levels increased. Cyanobacterial abundance was only elevated at extremely high levels of pCO2 (>1400 μatm). This is the first demonstration of the tolerance of natural marine benthic microalgae assemblages to elevated CO2 in an ecosystem subjected to multiple environmental stressors. Our observations indicate that Mediterranean coastal systems will alter as pCO2 levels continue to rise, with increased photosynthetic standing crop and taxonomic shifts in microalgal assemblages.

Photosynthetic innovation broadens the niche within a single species - Marjorie R. Lundgren; Guillaume Besnard; Brad S. Ripley; Caroline E. R. Lehmann; David S. Chatelet; Ralf G. Kynast; Mary Namaganda; Maria S. Vorontsova; Russell C. Hall; John Elia; Colin P. Osborne; Pascal‐Antoine Christin (Ecology Letters, 2015)
Adaptation to changing environments often requires novel traits, but how such traits directly affect the ecological niche remains poorly understood. Multiple plant lineages have evolved C 4 photosynthesis, a combination of anatomical and biochemical novelties predicted to increase productivity in warm and arid conditions. Here, we infer the dispersal history across geographical and environmental space in the only known species with both C 4 and non‐C 4 genotypes, the grass Alloteropsis semialata . While non‐C 4 individuals remained confined to a limited geographic area and restricted ecological conditions, C 4 individuals dispersed across three continents and into an expanded range of environments, encompassing the ancestral one. This first intraspecific investigation of C 4 evolutionary ecology shows that, in otherwise similar plants, C 4 photosynthesis does not shift the ecological niche, but broadens it, allowing dispersal into diverse conditions and over long distances. Over macroevolutionary timescales, this immediate effect can be blurred by subsequent specialisation towards more extreme niches.

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Temperate and tropical brown macroalgae thrive, despite decalcification, along natural CO 2 gradients - Vivienne R. Johnson; Bayden D. Russell; Katharina E. Fabricius; Colin Brownlee; Jason M. Hall‐Spencer (Global Change Biology, 2012)
Predicting the impacts of ocean acidification on coastal ecosystems requires an understanding of the effects on macroalgae and their grazers, as these underpin the ecology of rocky shores. Whilst calcified coralline algae (Rhodophyta) appear to be especially vulnerable to ocean acidification, there is a lack of information concerning calcified brown algae (Phaeophyta), which are not obligate calcifiers but are still important producers of calcium carbonate and organic matter in shallow coastal waters. Here, we compare ecological shifts in subtidal rocky shore systems along CO 2 gradients created by volcanic seeps in the Mediterranean and Papua New Guinea, focussing on abundant macroalgae and grazing sea urchins. In both the temperate and tropical systems the abundances of grazing sea urchins declined dramatically along CO 2 gradients. Temperate and tropical species of the calcifying macroalgal genus Padina (Dictyoaceae, Phaeophyta) showed reductions in Ca CO 3 content with CO 2 enrichment. In contrast to other studies of calcified macroalgae, however, we observed an increase in the abundance of Padina spp. in acidified conditions. Reduced sea urchin grazing pressure and significant increases in photosynthetic rates may explain the unexpected success of decalcified Padina spp. at elevated levels of CO 2 . This is the first study to provide a comparison of ecological changes along CO 2 gradients between temperate and tropical rocky shores. The similarities we found in the responses of Padina spp. and sea urchin abundance at several vent systems increases confidence in predictions of the ecological impacts of ocean acidification over a large geographical range .

A multinational study of neurological performance in antiretroviral therapy-naïve HIV-1-infected persons in diverse resource-constrained settings - Kevin Robertson; Johnstone Kumwenda; Khuanchai Supparatpinyo; Jeanne H. Jiang; Scott Evans; Thomas B. Campbell; Richard W. Price; Robert Murphy; Colin Hall; Christina M. Marra; Cheryl Marcus; Baiba Berzins; et al. (Journal of NeuroVirology, 2011)

Protein changes in CSF of HIV-infected patients: evidence for loss of neuroprotection - Rick B. Meeker; Winona Poulton; Silva Markovic-Plese; Colin Hall; Kevin Robertson (Journal of NeuroVirology, 2011)

Ligand-Binding Mass Spectrometry to Study Biotransformation of Fusion Protein Drugs and Guide Immunoassay Development: Strategic Approach and Application to Peptibodies Targeting the Thrombopoietin Receptor - Michael P. Hall; Colin Gegg; Kenneth Walker; Christopher Spahr; Robert Ortiz; Vimal Patel; Steven Yu; Liana Zhang; Hsieng Lu; Binodh DeSilva; Jean W. Lee (The AAPS Journal, 2010)

A novel extended family of stromal thioredoxins - Peter Cain; Michael Hall; Wolfgang P. Schröder; Thomas Kieselbach; Colin Robinson (Plant Molecular Biology, 2009)

Six new recombinant inbred populations for the study of quantitative traits in Arabidopsis thaliana - Carmel M. O’Neill; Colin Morgan; Jane Kirby; Hendrik Tschoep; Polo Xiaoyi Deng; Mahon Brennan; Ulises Rosas; Fiona Fraser; Caroline Hall; Samantha Gill; Ian Bancroft (Theoretical and Applied Genetics, 2008)

Six new recombinant inbred populations for the study of quantitative traits in Arabidopsis thaliana - Carmel M. O’Neill; Colin Morgan; Jane Kirby; Hendrik Tschoep; Polo Xiaoyi Deng; Mahon Brennan; Ulises Rosas; Fiona Fraser; Caroline Hall; Samantha Gill; Ian Bancroft (Theoretical and Applied Genetics, 2008)

Extent of the last ice sheet in northern Scotland tested with cosmogenic 10 Be exposure ages - William M. Phillips; Adrian M. Hall; Colin K. Ballantyne; Steven Binnie; Peter W. Kubik; Stewart Freeman (Journal of Quaternary Science, 2008)
The extent of the last British–Irish Ice Sheet (BIIS) in northern Scotland is disputed. A restricted ice sheet model holds that at the global Last Glacial Maximum (LGM; ca. 23–19 ka) the BIIS terminated on land in northern Scotland, leaving Buchan, Caithness and the Orkney Islands ice‐free. An alternative model implies that these three areas were ice‐covered at the LGM, with the BIIS extending offshore onto the adjacent shelves. We test the two models using cosmogenic 10 Be surface exposure dating of erratic boulders and glacially eroded bedrock from the three areas. Our results indicate that the last BIIS covered all of northern Scotland during the LGM, but that widespread deglaciation of Caithness and Orkney occurred prior to rapid warming at ca. 14.5 ka. Copyright © 2008 John Wiley & Sons, Ltd.

Second assessment of NeuroAIDS in Africa - Kevin Robertson; Kathy Kopnisky; James Hakim; Concepta Merry; Noeline Nakasujja; Colin Hall; Moussa Traore; Ned Sacktor; David Clifford; Charles Newton; Annelies Van Rie; Penny Holding; et al. (Journal of NeuroVirology, 2008)

Assessment of NeuroAIDS in the International Setting - Kevin R. Robertson; Colin D. Hall (Journal of Neuroimmune Pharmacology, 2007)

Impact of human immunodeficiency virus (HIV) subtypes on HIV-associated neurological disease - Kevin J Liner; Colin D Hall; Kevin R Robertson (Journal of NeuroVirology, 2007)

Cerebrospinal fluid from human immunodeficiency virus–infected individuals facilitates neurotoxicity by suppressing intracellular calcium recovery - Rick B Meeker; Jeramiah C Boles; Kevin R Robertson; Colin D Hall (Journal of NeuroVirology, 2005)

PHONING HOME‐A NEW GSM MOBILE PHONE TELEMETRY SYSTEM TO COLLECT MARK‐RECAPTURE DATA - Bernie Mcconnell; Rory Beaton; Ed Bryant; Colin Hunter; Phil Lovell; Ailsa Hall (Marine Mammal Science, 2004)
A bstract We describe and evaluate a new telemetry system based on GSM (Global System for Mobile Communications) mobile phone technology that may provide mark‐recapture data for single year survivorship studies. These phone‐tags automatically attempt to send an SMS text message once every two days. The successful receipt of a text message ashore constitutes a resighting event within the coastal zone of GSM coverage. Haul‐out data and coastal location data are incorporated into the messages. Data are presented for a three‐month period (January‐March) following tag deployment on 59 gray seal ( Halichoerus grypus ) pups at the Isle of May (Scotland). An average of 15.5, 4.1, and 8.2 seals succeeded in registering within each three‐day period in January, February, and March, respectively. Tags registered with a wide geographical range of GSM radio cells on the Scottish and English east coasts, and also from Norway and Germany. Haulout records covering 54% of the animals' time were received. With future modifications to the tags, this figure should approach 100%. The median delay to network registration was 9.6 sec from a seal in the sea (not hauled out). These data show that GSM mobile phone telemetry is a useful technique to obtain haul‐out and mark‐recapture data.

Localisation of phosphatidylethanolamine-binding protein in the brain and other tissues of the rat - Jan Frayne; Colin Ingram; Seth Love; Len Hall (Cell and Tissue Research, 1999)

Mid- and late-Holocene vegetation history and tephra studies at Fenton Cottage, Lancashire, U.K. - Colin Wells; Elizabeth Huckerby; Valerie Hall (Vegetation History and Archaeobotany, 1997)